Inverse relationship between anemia in the third trimester of pregnancy and low birth weight in a reference maternity unit of a carribean region of Colombia (2020)
Anemia is common amongst women in developing countries. Although a relationship has been established between gestational anemia and negative perinatal outcomes, it remains a controversial debate as opposite associations have been found. This study assessed the relationship between gestational anemia in the third trimester and low birth weight (LBW) in the ESE Clinica Maternidad Rafael Calvo, a reference maternity unit in the department of Bolivar, Colombia.